2007
DOI: 10.1007/s10482-007-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces sudanensis sp. nov., a new pathogen isolated from patients with actinomycetoma

Abstract: Nine strains isolated from mycetoma patients and received as Streptomyces somaliensis were the subject of a polyphasic taxonomic study. The organisms shared chemical markers consistent with their classification in the genus Streptomyces and formed two distinct monophyletic subclades in the Streptomyces 16S rRNA gene tree. The first subclade contained four organisms, including the type strain of S. somaliensis, and the second clade the remaining five strains which had almost identical 16S rRNA sequences. Member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…They can, however, be caused by S. somaliensis and S. sudanensis (497,498). The majority of invasive Streptomyces infections are associated with bacteremia and lung infections, namely, pneumonia, abscess, and pneumonitis (499).…”
Section: Interactions Between Actinobacteria and Vertebratesmentioning
confidence: 99%
“…They can, however, be caused by S. somaliensis and S. sudanensis (497,498). The majority of invasive Streptomyces infections are associated with bacteremia and lung infections, namely, pneumonia, abscess, and pneumonitis (499).…”
Section: Interactions Between Actinobacteria and Vertebratesmentioning
confidence: 99%
“…Streptomyces is a representative of a filamentous bacteria responsible for producing variety of valuable secondary metabolites, such as antibiotics, parasiticides, herbicides, and pharmacologically active substances, including antitumor agents and immunosuppressants (Waksman and Woodruff, 1940;Ditsler et al, 1992;Euverink, 1995;Newman et al, 2000;El Hassan et al, 2001;Bentley et al, 2002;Bibb, 2005;Quintana et al, 2008;Li et al, 2009;Doroghazi et al, 2014). Genome sequencing analyses of Streptomyces avermitilis (Omura et al, 2001), Streptomyces coelicolor A3(2) (Bentley et al, 2002), Streptomyces griseus IFO 13350 (Ohnishi et al, 2008), and Streptomyces bingchenggensis (Wang et al, 2010) revealed that Streptomyces possess an unexpected abundance of natural product biosynthetic gene clusters and thus that they have the potential to make many more compounds than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…treptomyces somaliensis is a Gram-positive, aerobic, filamentous human-pathogenic actinomycete that is a significant cause of actinomycetoma (4,9). Actinomycetomas are severe and debilitating infections that can spread to affect deep tissue and bone and are characterized by the formation of tissue masses, which may result in tissue destruction and deformity and may be fatal without surgical intervention.…”
mentioning
confidence: 99%